Peran Badan Usaha Milik Desa Dalam Pencapaian Sustainable Development Goals (SDGs) Desa di Kecamatan Gilireng Kabupaten Wajo - Umi Kalsum (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2023)
Village Sustainable Development Goals (Village SDGs) serve as a development policy framework aimed at achieving sustainable rural development through improved community welfare and equitable economic growth. One of the key instruments supporting this objective is Village-Owned Enterprises (Badan Usaha Milik Desa or BUMDes). BUMDes are expected to drive rural economic development by managing local resources, increasing Village Original Revenue (PAD), creating employment opportunities, and expanding economic prospects for local communities. This study aims to analyze the role of BUMDes in supporting the achievement of Village SDGs, particularly Goal 8 concerning equitable village economic growth in Gilireng District, Wajo Regency. The research employed a qualitative descriptive approach. The study was conducted in Paselloreng Village, Lamata Village, and Polewalie Village. Data were collected through observation, interviews, documentation, and literature review. Data analysis was carried out through data reduction, data presentation, conclusion drawing, and verification. The findings indicate that the role of BUMDes in supporting the achievement of Village SDGs in Gilireng District has not yet been fully optimized. In terms of increasing Village Original Revenue (PAD), the contribution of BUMDes remains relatively low due to the limited number of business units and the managerial capacity of BUMDes administrators. Regarding employment creation, BUMDes have not significantly absorbed local labor because of the limited scale of business operations. Meanwhile, in expanding village economic opportunities, BUMDes have contributed positively through savings and loan services that provide capital access for community members to develop productive economic activities. However, the utilization of local potential and the development of village-based business units still require further strengthening. Therefore, enhancing managerial capacity, promoting business innovation, strengthening government support, and expanding partnerships are necessary to optimize the role of BUMDes in fostering sustainable and equitable rural economic growth.